Stable Isotopes Analyses Of Carbon-13 And Nitrogen-15 In Kelantan River Sediments - Zulkifli, Nur Zafirah (2019)
Intensification of sedimentation process has increased the vulnerability of Kelantan River to natural hazards (i.e., climate change and floods). Considering the impact of soil erosion to sedimentation, identification of source of erosion is important to Kelantan watershed management. Stable isotope of carbon and nitrogen, along with C/N ratio analysis were carried out to identify the potential source of sedimentation in Kelantan watershed. Samples were collected in July 2015 (Southwest Monsoon, SWM) representing dry season and January 2016 for the wet season (Northeast Monsoon, NEM). The samples were analyzed using Elementary Analysis Isotopic Ratio Mass Spectrometer (EA-IRMS) and Perkin Elmer 2400 Series II CHN Elemental Analyzer. The stable isotope of 13C suggested that C3 type plants are dominant in Kelantan watershed with statistically no significant difference between July and January.